Local administration of granulocyte macrophage colony-stimulating factor induces local accumulation of dendritic cells and antigen-specific CD8+ T cells and enhances dendritic cell cross-presentation. Issue 13 (24th March 2015) - Lee, Sung-Jong; Song, Liwen; Yang, Ming-Chieh; Mao, Chih-Ping; Yang, Benjamin; Yang, Andrew; Jeang, Jessica; Peng, Shiwen; Wu, T.-C.; Hung, Chien-Fu
Abstract: Immunotherapy has emerged as a promising treatment strategy for the control of HPV-associated malignancies. Various therapeutic HPV vaccines have elicited potent antigen-specific CD8+ T cell mediated antitumor immune responses in preclinical models and are currently being tested in several clinical trials. Recent evidence indicates the importance of local immune activation, and higher number of immune cells in the site of lesion correlates with positive prognosis. Granulocyte macrophage colony-stimulating factor (GMCSF) has been reported to posses the ability to induce migration of antigen presentation cells and CD8+ T cells. Therefore, in the current study, we employ a combination of systemic therapeutic HPV DNA vaccination with local GMCSF application in the TC-1 tumor model. We show that intramuscular vaccination with CRT/E7 DNA followed by GMCSF intravaginal administration effectively controls cervicovaginal TC-1 tumors in mice. Furthermore, we observe an increase in the accumulation of E7-specific CD8+ T cells and dendritic cells in vaginal tumors following the combination treatment. In addition, we show that GMCSF induces activation and maturation in dendritic cells and promotes antigen cross-presentation. Our results support the clinical translation of the combination treatment of systemic therapeutic vaccination followed by local GMCSF administration as an effective strategy for tumor treatment.